Ảnh hưởng của công nghệ Blockchain đến ý định mua thực phẩm của người tiêu dùng tại Hà Nội, Việt Nam - Nguyễn Thị Phương, Linh; Đỗ Thị Hiền, Mai; Trần Thị Ngọc , Diệp; Hoàng Thị Mỹ, Linh; Nguyễn Đăng Nhật , Minh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
The combination of the Stimulus-Organism-Response (SOR) model with a quantitative research method - a broad survey of 244 consumers living in Hanoi, Vietnam. The authors aim to demonstrate the influence of Blockchain’s traceability on consumers’ intention to purchase food products. Through analysis using SPSS 26.0, the research results indicated that Blockchain traceability enhanced food quality, safety, and food fraud prevention, consequently had a positive impact on consumer trust and purchase intention. Based on these findings, the authors provided recommendations for authorities and businesses to promote the application of Blockchain in enhancing consumer trust and purchase intention.